Peranan Isteri yang Cakap dalam Keluarga Kristen Menurut Amsal 31:10–31 - Cahyadi, Kezia Verena (Sekolah Tinggi Teologia Kerusso Indonesia, 2020)
Being a wife is a high and honorable calling is not a negative and low in God’s plan. Wife or woman is a person specially prepared to fulfill her calling and play her role in the family as a wife and as the mother of the children. A woman can only find her true identity by knowing her role in the family that God has given and assigned to her. There is a saying that says “behind a successful man, there is always a strong woman”, this is the fulfillment of God’s design and purpose for creating a woman, which is to be a suitable helper for a man.